Scientific production in management accounting: bibliometric study at a national congress of accounting sciences (Revista Brasileira de Contabilidade e Gestão, 2017)
The objective of this article is to identify the characteristics of the publications made on Management Accounting in the USP Congress between 2010 and 2014. An appreciation of the articles was made, based on the model of Lunkes, Feliu and Rosa (2012). The research is empirical-analytical, exploratory and was used of descriptive statistical methods. As main results, it is verified that the publications in managerial accounting correspond to 23% of the total, with a gradual decrease in the five years analyzed. This result corroborates previous research suggesting his loss of space in the academy. It was identified the growth of female participation as the first author in the analyzed articles, as well as the increasing use of references to international journals, as well as the decrease in citations from books, evidencing the maturation of researchers in the area. On the other hand, it was observed a high average age of the referenced studies, 12 years, suggesting that the researchers of the area are not giving due attention to the new findings, since, the managerial accounting is in increasing and constant evolution. Most commonly used research strategies are survey surveys (33%) or documentary studies (30%). Regarding classification in themes, it was verified that the most studied lines of research are planning and control, followed by costs. Among the topics most frequently explored are: strategic management, analysis of indicators and measurement and performance evaluation. Finally, it is suggested that despite the improvements observed, the managerial accounting is an area that needs a clear personality for the studies, as well as of methodological deepening.
Keywords: scientific production; management accounting; USP Congress